Conservative Opposition to Climate Policy May be Partially Threat‐Based: A Test and Critique of the Integrated Threat Model of Climate Attitudes - Stanley, Samantha K.; Leviston, Zoe; Jylhä, Kirsti M.; Walker, Iain (Journal of applied social psychology, 2025)
ABSTRACT One explanation for the link between political conservatism and rejection of the science and solutions of climate change is based on perceived threats. Yet, until recently, this claim has not been studied by simultaneously considering the different levels at which individuals may experience a sense of threat (i.e., threat of climate change or climate policy, at personal or collective level, on economic or cultural domains). A recent theoretical advance integrated the existing threat‐based explanations for conservatives' lower acceptance of climate change and support for pro‐climate policy. We aimed to subject aspects of this integrated threat model of climate change attitudes to empirical testing through a series of three studies (Study 1 N = 5110, Study 2 N = 299, Study 3 N = 552). We found the hypothesized threat asymmetry in risk assessments of climate change and its solutions, whereby conservative ideologies predict greater perceived threat from climate policy, and lower perceived threat from climate change itself. Also consistent with the model, we found evidence that cross‐sectionally, threat partially mediated associations between ideology and policy support. However, we also report on an unsuccessful experimental test of the model. Prompting people to think about the economic or cultural consequences of climate policy did not heighten conservatives' perceptions of policy threat (i.e., a manipulation failure), and thus did not have the expected exacerbating effect on their climate policy concern. Findings suggest conservatives' threat‐based concerns about climate policy may be difficult to shift experimentally and provide only a partial explanation for their lower policy support.